The Forgotten Disc: Synthesis and Recommendations for Viable VCD Preservation - Andrew Weaver; Ashley Blewer (Code4Lib Journal)
As optical media held by cultural heritage institutions has fully transitioned from use as a digital preservation ‘solution’ to a digital preservation risk, an increasing amount of effort has been focused on exploring tools and workflows to migrate the data off of these materials before it is permanently lost to physical degradation. One optical format, however, has been broadly ignored by the existing body of work: the humble Video CD. While never a dominant format in the Anglosphere, the Video CD, or VCD, held wide popularity from the 1990s through the 2000s in Asia and other regions. As such, a dedicated exploration of preservation solutions for VCD has utility both as a resource for institutions that collect heavily in Pacific Rim materials, as well as a means to, in a minor way, aid in the ongoing efforts to expand the Digital Preservation corpus beyond its traditional focus of issues prevalent in North America and Europe. This paper introduces an overview of VCD as a format and summarizes its unique characteristics that impact preservation decisions and presents the results of a survey of existing tools and methods for the migration of VCD contents. This paper conveys practical methods for migrating VCD material from the original carrier and into both digital preservation and access workflows.